Budapest as a destination of migration: the view of transnational creative workers - Egedy, Tamás; Kovács, Zoltán (Hungarian Geographical Bulletin, 2011)
Creativity, knowledge and innovation are broadly recognised as the essential ingredients of economic success in the advanced capitalist world. Concerning further development of Europe it might be decisive how the metropolitan regions will be able to attract and integrate firms in the sphere of the creative economy and their manpower. In this process highly skilled transnational migrants play an ever increasing role and they contribute actively to the international competitiveness of cities. Based on the results of empirical research we trie to assess those triggers and motivations that are decisive in attracting and settling down of transnational migrants in Budapest. Ex-pats living and working in Budapest expressed their opinions and criticism about hard and soft factors provided by the city. The paper highlights the most relevant findings about how foreign creative workers see the city and how they evaluate its potentials, strengths and weaknesses. At the end of the paper few recommendations are formulated for decision-makers to make Budapest more attractive for creative transnational migrants.